Uma resenha sobre modelos de apreçamento de derivativos - Guimarães, Pedro Henrique Engel (2012)
I present here an approach that unify a variety of derivative pricing models that consists of attaining a Partial Diﬀerential Equation(PDE) by intuitive arguments and give its solution by Feynman-Kac method as a conditinal expectation of a markovian process. The expectation is taken in a risk neutral world(or risk neutral measure) where all the assets grow at the risk free rate. I also present how to make this speciﬁc change of measure, connecting the real world to the risk neutral world, and show that the relevant element for the measure change is the market price of factor risk. When the market is complete the market price of risk is unique and when the market is incomplete there is a variety of possible prices to the market price of factor risks that satisfy no arbitrage arguments. In the latter case the parameters are usually chosen to calibrate the model to market data.